An examination of the interplay between country-of-origin, brand equity, brand preference and purchase intention toward global fashion brands. (2018) - Pool, Javad Khazaei; Asian, Sobhan; Abareshi, Ahmad; Mahyari, Hamze Kazemi
This study aims to propose and empirically test a behavioural model of consumer perceptions of country-of-origin, brand equity, brand preference and purchase intention in the context of fashion brands in Iran. To provide a detailed understanding of customers' perceptions of purchase intention, a survey study was conducted. The research model is validated, and the developed hypotheses are tested using a structural equation model (SEM). Country-of-origin is shown to be positively associated with brand equity. Consistent with expectations, our results reveal that brand equity influences brand preference and purchase intention. Findings also support the hypothesised relationship between brand preference and purchase intention. The present research is one of the pioneer studies that highlight the importance of purchase intention with regard to fashion brands in promoting a luxury market. This study contributes to the literature by developing and testing a comprehensive research model using SEM and offers important guidelines to international marketers who are planning to introduce their fashion brands to the Iranian market.